Vocabulary Development of Junior Teens - L. V. Nikonova (Russian State Vocational Pedagogical University, 2015)
The article deals with the communicative competence formation of young adolescents in the secondary school at the Russian language lessons. The author maintains that the key element of the above problem is the vocabulary development guaranteeing both comprehension and verbal expression formation - oral and written. The theoretical part of the research explores different word functions: nominal, communicative, text generating and semantic. The correlation between the mental development level and lexical semantic system formation is emphasized. The age specific features of junior teens are listed: rising interest to various life spheres and activi- ties, capability of formulating opinions and judgments, self-awareness, formation of values. The relationship complexity stimulates vocabulary development of 10 to 12 year-old children; however, the process requires peda- gogical facilitation.The monitoring of speech development proves the necessity of commutative competence formation of the fifth- and sixth-year pupils. The paper presents the model of communicative competence development and its approbation results received for the junior adolescents.